Estudio y difusión comunicacional de las manifestaciones culturales del cantón Piñas, de la provincia de El Oro, en el periodo julio – octubre del 2012. Propuesta alternativa - Ayala Torres, Narcisa Jackeline (2014)
This research makes a compilation of the cultural manifestations of the canton pineapples, with the aim of contributing to disseminate each one of the customs, traditions, religious festivals, music, art, among other manifestations that encompasses the culture of the canton pineapples, these are intended to be informed through the media (print media, and Radio). However the institutions responsible for the dissemination of culture as the decentralized autonomous Municipal Government and the House of Culture "Benjamín Carrión, there is ignorance of processes and communicational strategies that allow the information and communication of the different cultural manifestations of the city These strategies and communication processes will allow you to transmit and communicate the cultural manifestations of the canton, through leaflets, magazines, radio program with the collaboration and dissemination of the media, these are the communications links appropriate to the cultural diffusion, With the objective that the citizens and tourists know and asking about each of the cultural manifestations that identify the inhabitants pinasienses. The space in which this research is developing in the canton pineapples, of the Province of El Oro. Through the work and field study it is concluded that the information generated by the institutions responsible for the cultural diffusion is abysmal , due to the absence of communication processes, this has generated that citizenship is unaware in great part the cultural manifestations. Resulting data as important the role of institutions to safeguard political interest, more does not disseminate the cultural manifestations of the city.